Synthesis and Preliminary In Vitro and In Vivo Evaluation of Thiirane‐Based Slow‐Binding MMP Inhibitors as Potential Radiotracers for PET Imaging. Issue 42 (9th November 2018) - Hohn, Michael; Chang, Mayland; Meisel, Jayda E.; Frost, Emma; Schwegmann, Katrin; Hermann, Sven; Schäfers, Michael; Riemann, Burkhard; Haufe, Günter; Breyholz, Hans‐Jörg; Wagner, Stefan
Abstract: Many serious diseases such as cancer, atherosclerosis and arthritis are characterized by upregulation of activated matrix metalloproteinases (MMPs). For this reason imaging and quantification of activated MMPs with the molecular imaging techniques such as single photon emission computed tomography (SPECT) and positron emission tomography (PET) using radiolabeled MMP inhibitors would be a valuable tool for the diagnosis and therapy planning of mentioned diseases. This work aims at the synthesis and preliminary in vitro and in vivo evaluation of positron‐emitter 18 F‐fluorine labeled radiotracers based on 2‐{[(4‐phenoxyphenyl)sulfonyl]methyl}thiirane (SB‐3CT), a slow‐binding and mechanism‐based MMP‐2 and −9 inhibitor. Therefore, a library of fluorinated SB‐3CT derivatives were prepared and evaluated in vitro in MMP inhibition assays. From this pool the 18 F‐labeled triazole [ 18 F]18d was successfully synthesized in a two‐step procedure. However, this compound was unstable in human and mouse serum and showed a biodistribution behavior in C57BL/6 mice that is not favorable for PET imaging preventing further in vivo evaluations in MMP‐associated mouse models of disease. Abstract : Imaging of matrix metalloproteinases (MMPs) dysregulated in a multitude of diseases with positron emission tomography (PET) is of great clinical interest. For the first time the thiirane‐based SB‐3CT, exhibiting the unique characteristic of slow‐binding inhibition of MMP‐2 and −9, served as lead structure for 18 F‐labeled radiotracer development. The first representative of this compound class ([ 18 F]18d) was evaluated in vitro and in vivo .